2019
DOI: 10.1111/jpn.13180
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol induces oxidative stress, inflammatory response and apoptosis in bovine mammary epithelial cells

Abstract: Deoxynivalenol (DON) is a toxic secondary metabolite produced by Fusarium graminearum. It is one of the most common feed contaminants that poses a serious threat to the health and performance of dairy cows. This study investigated the in vitro cytotoxicity of DON on bovine mammary epithelial cells (MAC‐T). DON at different concentrations (0.25, 0.3, 0.5, 0.8, 1 or 2 μg/ml) inhibited the growth of MAC‐T cells after 24 hr of exposure (p < .001). DON at 0.25 μg/ml increased lactate dehydrogenase (LDH) leakage (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 52 publications
1
15
1
Order By: Relevance
“…Regarding the in vitro studies, a recent work by Pauletto et al [93] on bovine hepatocytes reported a significant increase in MDA concentration in incubated cells with AFB1, while their transcriptional profile of antioxidant enzymes (CAT, SOD, GSH-Px) were not affected. Two comparable studies conducted in vitro in bovine mammary epithelia cells that were treated with DON (0.25 µg/mL) for 24 h showed an increase in the concentration of MDA while TAC and GSH portrayed a decrease [94,95]. More specifically, Wang et al [94] reported a lower activity of the SOD enzyme and Zhang et al [95] observed the same trend in transcript levels (SOD1 and SOD2).…”
Section: The Effect Of Mycotoxins On the Antioxidant Status Of Ruminantsmentioning
confidence: 83%
See 1 more Smart Citation
“…Regarding the in vitro studies, a recent work by Pauletto et al [93] on bovine hepatocytes reported a significant increase in MDA concentration in incubated cells with AFB1, while their transcriptional profile of antioxidant enzymes (CAT, SOD, GSH-Px) were not affected. Two comparable studies conducted in vitro in bovine mammary epithelia cells that were treated with DON (0.25 µg/mL) for 24 h showed an increase in the concentration of MDA while TAC and GSH portrayed a decrease [94,95]. More specifically, Wang et al [94] reported a lower activity of the SOD enzyme and Zhang et al [95] observed the same trend in transcript levels (SOD1 and SOD2).…”
Section: The Effect Of Mycotoxins On the Antioxidant Status Of Ruminantsmentioning
confidence: 83%
“…Two comparable studies conducted in vitro in bovine mammary epithelia cells that were treated with DON (0.25 µg/mL) for 24 h showed an increase in the concentration of MDA while TAC and GSH portrayed a decrease [94,95]. More specifically, Wang et al [94] reported a lower activity of the SOD enzyme and Zhang et al [95] observed the same trend in transcript levels (SOD1 and SOD2). In both experimental trials, despite the negative oxidative status that was observed, immunomodulating genes related to pro-inflammatory responses were reported in higher expression levels, suggesting a cytokine storm.…”
Section: The Effect Of Mycotoxins On the Antioxidant Status Of Ruminantsmentioning
confidence: 83%
“…However, as the dose and time of DON exposure increase, the redox balance may be disrupted. For example, 0.25 μg/mL DON can cause a decrease in total superoxide dismutase (T-SOD) activity and glutathione (GSH) levels and increase reactive oxygen species (ROS) and malondialdehyde (MDA) levels [ 10 ]. When the diet of mice was contaminated with DON, the activities of CAT and SOD in the liver decreased, while the content of MDA increased [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, in gilts, this was a compensatory mechanism due to the low GSS expression in mature oocytes. Both DON [ 50 ] and BEA [ 51 ] induce oxidative stress and also decrease the capacity to synthesize GSH, partly explaining the high susceptibility of gilt COCs to these mycotoxins during maturation.…”
Section: Discussionmentioning
confidence: 99%